2011
DOI: 10.1089/vbz.2010.0262
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Mosquitoes and Mosquito-Borne Arboviruses in Inner Mongolia, China

Abstract: During summers in 2007 and 2008, an investigation was conducted to identify the distribution of mosquitoes and circulation of mosquito-borne arboviruses in Inner Mongolia, China. A total of 10,542 mosquitoes consisting of seven species from the Aedes, Culex, and Anopheles genera were trapped by UV-light traps, and they were sorted into 211 pools according to species, location, and date of collection. The result showed that Aedes dorsalis was the most common species, accounting for 41.0% (4327/10,542) of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…pipiens pallens followed by Ae. albopictus, were also found in most of the provinces studied, which confirms previous reports on these species' high prevalence and widespread distribution in China (Cao et al 2011, Wang et al 2011, Feng et al 2012, Guo et al 2014, Huang et al 2015.…”
Section: Discussionsupporting
confidence: 89%
“…pipiens pallens followed by Ae. albopictus, were also found in most of the provinces studied, which confirms previous reports on these species' high prevalence and widespread distribution in China (Cao et al 2011, Wang et al 2011, Feng et al 2012, Guo et al 2014, Huang et al 2015.…”
Section: Discussionsupporting
confidence: 89%
“…C. pipiens was identified only once as vector for TAHV (Arcan et al 1974), and in three studies TAHV was found in Culex modestus mosquitoes (Danielová and Holubová 1977, Hubálek et al 2010, Cao et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…TAHV was first described in 1958 in the Czech Republic (Bardos et al 1959). In the following decades, TAHV was isolated from mosquitoes from eastern Austria (Aspöck andKunz 1971, Pilaski andMackenstein 1985), southern Germany Ackermann 1972, Spieckermann andAckermann 1974), and southeastern Germany (Pilaski and Mackenstein 1985) as well as from northern Italy, Hungary, China, Mongolia, and again the Czech Republic (Molnár et al 1973, Pilaski and Mackenstein 1985, Lu et al 2009, Hubálek et al 2010, Cao et al 2011. Furthermore, the virus was also identified in Croatia, Serbia, and Romania (Drȃgȃnescu and Gîrjabu 1979, Vesenjak-Hirjan et al 1991, Madić et al 1993 as well as in the Russian Republic of Karelia as the most northern point of detection (Ĺ vov et al 1977).…”
Section: Introductionmentioning
confidence: 99%
“…In the summer of 2007 and 2008, an investigation was conducted to identify the distribution of mosquitoes and the circulation of mosquito-borne arboviruses in Inner Mongolia, China (Cao et al 2011). Ae.…”
Section: Discussionmentioning
confidence: 99%